2017
DOI: 10.17221/4/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of LC/HRPS for quantification of adenine nucleotides, creatine phosphate, and creatine in sturgeon spermatozoa

Abstract: Fedorov P., Grabic R., Fedorova G., Cosson J., Boryshpolets S., Dzyuba B. (2017): Development and application of LC/HRPS for quantification of adenine nucleotides, creatine phosphate, and creatine in sturgeon spermatozoa. Czech J. Anim. Sci., 62, 67-74.The objective of this study was to investigate the applicability of liquid chromatography coupled with high resolution product scan (LC/HRPS) mass spectrometry for simultaneous quantification of adenine nucleotides, creatine phosphate, and creatine levels after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In fish, creatine phosphate (CrP) is the main high-energy compound that was characterized in spermatozoa of several fish species as a complement of ATP [74,79,85]. In the last decades, many studies have demonstrated the decrease of the ATP concentration inside the fish sperm cells during the motility period [39, 67,74,76,79,85,90,91,93,100]. A more restricted number of studies have investigated the concentration of ATP related compound such as ADP, AMP, CrP, and others [74,79,85,100].…”
Section: Other Energetic Molecules Assisting Atp Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…In fish, creatine phosphate (CrP) is the main high-energy compound that was characterized in spermatozoa of several fish species as a complement of ATP [74,79,85]. In the last decades, many studies have demonstrated the decrease of the ATP concentration inside the fish sperm cells during the motility period [39, 67,74,76,79,85,90,91,93,100]. A more restricted number of studies have investigated the concentration of ATP related compound such as ADP, AMP, CrP, and others [74,79,85,100].…”
Section: Other Energetic Molecules Assisting Atp Maintenancementioning
confidence: 99%
“…In the last decades, many studies have demonstrated the decrease of the ATP concentration inside the fish sperm cells during the motility period [39, 67,74,76,79,85,90,91,93,100]. A more restricted number of studies have investigated the concentration of ATP related compound such as ADP, AMP, CrP, and others [74,79,85,100]. All these compounds are part of an intracellular network under control of different enzymes that are able to transfer high-energy phosphate bonds from one to another (see Figure XX in Chapter 1 of Cosson [21]), for example, the equilibrium ATP< = >ADP + Pi is catalyzed by enzymes called ATPases.…”
Section: Other Energetic Molecules Assisting Atp Maintenancementioning
confidence: 99%
See 1 more Smart Citation
“…We found cryopreservation to be associated with a 27.5% lower creatine kinase activity black-lip pearl oyster spermatozoa compared to fresh. It was also shown that enzyme activity, including creatine kinase activity, was involved in flagellar mobility and thus represents an indicator of sperm quality, as reported in sea urchin Shapiro 1985, 1989;Wallimann et al 1986;Tombes et al 1987;Wallimann and Hemmer 1994;van Dorsten et al 1997;Wallimann et al 2011), rainbow trout O. mykiss (Saudrais et al 1998) and sturgeon A. ruthenus (Fedorov et al 2017). Cryopreservation has been reported to affect enzyme activity in marine fish.…”
Section: Discussionmentioning
confidence: 84%
“…Motile spermatozoa should present a high mitochondrial respiration rate, allowing high ATP production. It was demonstrated in sea urchin Shapiro 1985, 1989;Tombes et al 1987;Walliman et al 2011;Ingermann et al 2011) that creatine-phosphate stores and creatine kinase activity are related the flagellar motility (Saudrais et al 1998;Dzyuba et al 2017;Fedorov et al 2017). van Dorsten et al (1997 showed that, in sea urchin sperm, creatine kinase activity is related to energy metabolism (O 2 consumption and ATP production).…”
Section: Discussionmentioning
confidence: 99%